STRATEGI PENGELOLAAN LINGKUNGAN : FAKTOR-FAKTOR YANG MEMPENGARUHI DAN DAMPAKNYA TERHADAP KEUNGGULAN BERSAING YANG BERKELANJUTAN (Studi Kasus Pada Industri Mebel di Jepara, Jawa Tengah) - Primasari, Dewi (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2015)
Furniture companies in Indonesia, that mostly a small medium enterprise was expected had adopted environmental management in their organization. The research problems in this research is how to increase sustainablecompetitive using corporate environmental management.Purpose of this research is to analyze relationship betweenregulation and environmental management, to analyzerelationship between stakeholder and environmentalmanagement, to analyze relationship between cost andenvironmental management, to analyze relationship betweencompetitive requirement and environmental, to analyzerelationship between environmental management andcompetitive advantage. Variable that supports this research comes from Bansal & Roth (2000), Berri & Rondinelli (1998), dan Starik & Marcus(2000). Sample used in this research are 120 responden. Theyare the furniture companies that categories as small enterprisewhich the employee about 5-99 person and 1 year minimumoperating in Jepara. Result of hypothesis examination prove that regulation havepositive impact to environmental management, cost have positiveimpact to environmental management, stakeholder pressure havean positive impact to environmental management, competitiverequirement have positive impact to environmental management,and environmental management have positive impact tosustainable competitive advantage for corporation.Pursuant to result examination of the hypothesis hence canpulled some managerial implication, that is company require togive to make product design partying to environment, companyown clear product standard which make customer satisfied,company give attention to public request for the environmentalprotection, company can make environmental management as away of to decrease expense, by decreasing waste or by recyclingexisting waste.